Construction project failure: Investigating causes of ineffective building information modelling execution plans - Mashanim, Mahazir; Rahimi, A. Rahman; Nurhaizan, Mohd Zainudin; Salmaliza, Salleh (Malaysian Institute of Planners, 2024)
The successful implementation of Building Information Modelling (BIM) is contingent upon effectively executing BIM Execution Plans (BEPs). This study aims to investigate the causes that contribute to the development of ineffective BEPs that ultimately result in construction project failures. Interview data with twenty BIM professionals were collected on causes contributing to the development of ineffective BEPs. The collected data was analyzed using thematic analysis. The analysis revealed three categories contributing to ineffective BEPs: people, process, and technology. There are 11, 6, and 1 causes related to people, process, and technology, respectively. The finding suggests that incompetency, lack of knowledge in BIM, individual attitude, poor data management, and insufficient technology used are the causes that contribute to ineffective BEPs. The outcomes of this study offer substantial insights into the Architecture, Engineering, and Construction (AEC) industry in developing effective BEPs, thereby ensuring the successful delivery of BIM-based construction projects.